Discrete spot laser hardening and remelting with a high-brilliance source for surface structuring of a hypereutectoid steel. (5th February 2017) - Tricarico, L.; Ancona, A.; Palumbo, G.; Sorgente, D.; Spina, R.; Lugarà, P.M.
Abstract: In this work the single-pulse laser irradiation of a hypereutectoid steel was investigated using a fiber laser source, in a range of process parameters enabling surface hardening and remelting. Effects of laser power, pulse energy and defocusing distance were investigated using a numerical/experimental approach. Laser surface treatments were conducted on uncoated samples without any gas shielding, changing both the laser power and the pulse energy, and exploring a wide range of defocusing distances. Numerical simulations were conducted using a finite element model calibrated by means of an optimization procedure based on a specific calculation algorithm and using a subset of experimental data producing surface melting. Using both simulations and experiments, the process operating windows of the discrete spot laser treatment were determined: it was found that, when varying the laser power between 250 W and 750 W, melt-free hardened zones are produced with a maximum extension between 0.7 mm and 1.0 mm; on the contrary, in case of more tightly beam focusing conditions, surface melting occurred with a size of the re-melted areas ranging between 1.0 mm and 1.4 mm. Results further showed that a small change (generally 2–3 mm) of the defocusing distance suddenly brings the material from melting to a non-hardening condition. Graphical abstract: Highlights: Process windows for spot hardening and melting determined Diameter and depth of the laser treated region numerically and experimentally evaluated Key parameters for the simulation evaluated fitting experimental data. The proposed tuning procedure based on multi-objective optimization revealed effective. The fabrication of bio-mimetic surfaces is possible implementing the process maps.